AS DECISÕES PARA A INSERÇÃO DA EFICIÊNCIA ENERGÉTICA EM PARQUE CONSTRUÍDO UNIVERSITÁRIO - Frandoloso, Marcos Antonio Leite (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Nowadays the growing interest about energy efficiency have become relevant both in terms of environmental and economic aspects. Some initiatives have been launched and have awakened environmental responsibility within the Universities; reference values and index In order to evaluate the positive and negative features lead, thereby, it was proposed a methodology that could verify its applicability at the University of Passo Fundo - Brazil. Four aspects have been developed: consumption of energy resources; comfort conditions; decision-making processes and efficiency reference indexes. A simulation using the software DesignBuilder was applied to obtain diagnosis of the real and ideal condition models. Since the present study identifies and assesses the evolution of incident factors towards energy consumption, it is expected that the university promotes a reflection about their practices to develop feasible tools, which contribute for sustainable measures. It is imperative that making-decision process follow guidelines to evaluate inversions and costs when measuring environmental management strategies and their whole implications. This paper contributes to the debate on universities policies, in an inclusive perspective about their infrastructure, consequently, its relation to concrete examples to improve the Education for Sustainability.